Intraclonal competitive fitness of longitudinal cystic fibrosis Pseudomonas aeruginosa airway isolates in liquid cultures. (7th February 2020) - Cramer, Nina; Fischer, Sebastian; Hedtfeld, Silke; Dorda, Marie; Tümmler, Burkhard
Summary: The metabolically versatile Pseudomonas aeruginosa inhabits biotic and abiotic environments including the niche of cystic fibrosis (CF) airways. This study investigated how the adaptation to CF lungs affects the within‐clone fitness of P. aeruginosa to grow and persist in liquid cultures in the presence of the clonal ancestors. Longitudinal clonal P. aeruginosa isolates that had been collected from 12 CF donors since the onset of colonization for up to 30 years was subjected to within‐clone competition experiments. The relative quantities of individual strains were determined by marker‐free amplicon sequencing of multiplex PCR products of strain‐specific nucleotide sequence variants, a novel method that is generally applicable to studies in evolutionary genetics and microbial ecology with real‐world strain collections. For 10 of the 12 examined patient courses, P. aeruginosa isolates of the first years of colonization grew faster in the presence of their clonal progeny than alone. Single growth of individual strains showed no temporal trend with colonization time, but in co‐culture, the early isolates out‐competed their clonal progeny. Irrespective of the genetic make‐up of the clone and its genomic microevolution in CF lungs, the early isolates expressed fitness traits to win the within‐clone competition that were absent in their progeny.